PRAKTIK PREMANISME DENGAN MEMBAWA NAMA ORGANISASI KEMASYARAKATAN DALAM PERSPEKTIF HUKUM PIDANA - Rinaldi Rinaldi (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTION Thugism is derived from the word thug, this term comes from the Dutch vrijman or freeman in English, which means free people, according to KBBI thugs are a term for bad guys such as jacks, robbers, extortionists, and so on, while thugs are a way or lifestyle like thugs, usually by promoting violence. Thugism that is often done in people's lives usually aims to get results through a fast or instantaneous way, the perpetrators of this act will usually get sanctions in the form of criminal sanctions, be it in the form of prison sentences, fines or social sanctions. Keywords : Thugism, Criminal, Sanction